Electroretinographic responses to periodic stimuli in primates and the relevance for visual perception and for clinical studies - Kremers, Jan; Huchzermeyer, Cord (Visual Neuroscience, 2024)
Currently, electroretinograms (ERGs) are mainly recorded while using flashes as stimuli. In this review, we will argue that strong flashes are not ideal for studying visual information processing. ERG responses to periodic stimuli may be more strongly associated with the activity of post-receptoral neurons (belonging to different retino-geniculate pathways) and, therefore, be more relevant for visual perception. We will also argue that the use of periodic stimuli may be an attractive addition to clinically available retinal electrophysiological methods.
CRIS-Team Scopus Importer:2024-12-06
Keywords: chromaticity; electroretinogram; luminance; psychophysics; repetitive stimuli; retino-geniculate pathways